Surface properties of calcium aluminate cement blends for bone repair applications. Issue 9 (15th June 2020) - Oliveira, I.R.; Barbosa, A.M.; Grancianinov, K.J.S.; Origo, F.D.; dos Santos, K.W.; Leite, P.M.S.C.M.; Raniero, L.J.; Pandolfelli, V.C.
Abstract: Surface composition and its roughness affect the interactions that induce bone tissue growth in a biomaterial. Irregular surfaces result in better bone fixation than smoother ones, indicating that this feature might have a direct influence on osteoblast adhesion. In this paper, some surface properties of calcium aluminate cement (CAC)-based blends were evaluated, compared to commercial products as mineral trioxide aggregate (MTA) and polimetylmethacrylate (PMMA) as a reference. Roughness was measured by profilometry using samples without or with SBF (simulated body fluid) treatment for 21 days. The collagen samples, MTA and PMMA, presented higher roughness values before SBF treatment. After SBF exposure, all samples except those with PMMA showed an increase in roughness, especially the MTA ones. Cell adhesion was observed by SEM after contact with mesenchymal cell cultures. The latter adhered to the sample's surface pointing out their biocompatibility. Finally, the interactions of samples with culture medium (Dulbecco's Modified Eagle Medium = DMEM) were measured for periods of 1, 3, 7, 14, and 21 days. The sample surfaces were evaluated by SEM, EDX, FTIR and XRD. After the contact of samples with culture medium, the calcium concentration was measured by atomic absorption spectroscopy. All CAC-based blends and mainly MTA presented precipitation after treatment with DMEM, which was characterized as calcium phosphate and mainly calcium carbonate.